2022
DOI: 10.1007/s00424-022-02719-2
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of mitochondrial temperature in health and disease

Abstract: Mitochondrial temperature is produced by various metabolic processes inside the mitochondria, particularly oxidative phosphorylation. It was recently reported that mitochondria could normally operate at high temperatures that can reach 50℃. The aim of this review is to identify mitochondrial temperature differences between normal cells and cancer cells. Herein, we discussed the different types of mitochondrial thermosensors and their advantages and disadvantages. We reviewed the studies assessing the mitochond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 84 publications
0
5
0
1
Order By: Relevance
“…To evaluate this activity, isolated mitochondria were subjected to different conditions and labeled with calcein-AM, and their fluorescence intensity was measured using nFCM to gauge esterase activity (Figure A). Recent studies indicate that human mitochondria can reach temperatures as high as 50 °C during intense metabolic processes such as oxidative phosphorylation, , suggesting that mitochondria might sustain efficient functionality at elevated temperatures. In contrast, photothermal therapy typically involves temperatures ranging from subcoagulative (43–55 °C) to coagulative (55–100 °C), aiming to induce rapid cell death through protein denaturation and cell membrane damage .…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate this activity, isolated mitochondria were subjected to different conditions and labeled with calcein-AM, and their fluorescence intensity was measured using nFCM to gauge esterase activity (Figure A). Recent studies indicate that human mitochondria can reach temperatures as high as 50 °C during intense metabolic processes such as oxidative phosphorylation, , suggesting that mitochondria might sustain efficient functionality at elevated temperatures. In contrast, photothermal therapy typically involves temperatures ranging from subcoagulative (43–55 °C) to coagulative (55–100 °C), aiming to induce rapid cell death through protein denaturation and cell membrane damage .…”
Section: Resultsmentioning
confidence: 99%
“…Mitochondrial temperature is a by-product of the OXPHOS which is intimately linked with the mitochondrial dysfunctions [53]. It has been reported that “Mitochondria are physiologically maintained at close to 50°C”, suggesting their warmer temperature than the surrounding [54].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, considering that heat generation is an inescapable cellular function of metabolically active mitochondria, a loss of this activity, as in cases of mitochondrial disease, may compromise the maintenance of intracellular temperature or induce futile cycles of cytosolic ATP generation and usage that may have profound metabolic effects. This could be a crucial aspect of mitochondrial pathology 66 and may also influence progression in other metabolic diseases, including cancer 67 . Some of these and related issues are discussed in the recent paper of Fahimi and colleagues 68 .…”
Section: Biological Implications Of High Mitochondrial Temperaturementioning
confidence: 99%